Green Innovation, Sustainability Growth Rate, and Firm Performance Evidence from Indonesia - Siagian, Harlyn; Siagian, Valentine (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The growing emphasis on environmental sustainability has prompted firms to adopt green innovation and sustainable growth strategies to enhance performance while addressing ecological concerns. This study investigates the impact of green innovation and sustainability growth rate on firm performance among Indonesian companies. Utilizing regression analysis with panel data from 2013 to 2022, sourced from the Bloomberg database, the research examines key performance metrics: return on assets, return on equity, and net profit margin. The findings indicate that green innovation negatively affects short-term financial performance, particularly return on assets and net profit margin, likely due to high initial costs of technology adoption and compliance. Conversely, the sustainability growth rate exhibits a strong positive correlation with all performance metrics, highlighting its role in enhancing profitability and operational efficiency. These results suggest that while green innovation may pose short-term financial challenges, prioritizing sustainable growth can yield significant long-term benefits. The study underscores the need for strategic implementation of green practices and supportive policies to balance environmental goals with financial viability, offering insights for policymakers and business leaders aiming to foster sustainable development in Indonesia’s industrial sector.